2013
DOI: 10.1111/1744-9987.12048
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Encapsulating Peritoneal Sclerosis in Long‐Term Peritoneal Dialysis: A Retrospective Observational Study

Abstract: Encapsulating peritoneal sclerosis (EPS) is a serious complication that occurs in patients with long-term peritoneal dialysis (PD). Investigation of risk factors that contribute to EPS in patients on long-term PD therapy is needed. In a retrospective, observational study, data were collected for 107 patients treated with PD therapy for more than 5 years. Fifty cases of EPS were compared with 57 cases of non-EPS. To evaluate the impact of PD-associated peritonitis in EPS, univariate and multivariate logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 24 publications
(48 reference statements)
2
21
0
Order By: Relevance
“…Further, largely known drug‐resistant microorganisms, such as MRSA, MRSE and fungi, tended to result in earlier PD cessation. As previously reported, a longer duration of peritonitis might contribute to the development of EPS .…”
Section: Discussionsupporting
confidence: 66%
“…Further, largely known drug‐resistant microorganisms, such as MRSA, MRSE and fungi, tended to result in earlier PD cessation. As previously reported, a longer duration of peritonitis might contribute to the development of EPS .…”
Section: Discussionsupporting
confidence: 66%
“…It is thought that EPS development becomes higher when total duration of peritonitis is over 36 days. We have previously reported, that in patients on long‐term PD therapy (over 60 months), the duration of peritonitis was independently associated with the development of EPS . Our data revealed that the duration of peritonitis was independently associated with the development of EPS regardless of PD duration.…”
Section: Discussionsupporting
confidence: 60%
“…'Recovery from peritonitis' was defined as being present if the above detailed criteria resolved. In addition, 'the duration of peritonitis' was defined as the period from diagnosis to recovery of peritonitis . Furthermore, 'total duration of peritonitis' was defined as the sum of 'the duration of peritonitis'.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, peritonitis presents a risk for the development of encapsulating peritoneal sclerosis (EPS) [6]. The duration of peritonitis is independently associated with EPS [7]. In particular, fungal and Pseudomonas infections put patients at a higher risk for the development of EPS [8].…”
Section: Introductionmentioning
confidence: 99%